Facing the facts confronting legislative facts in Supreme Court adjudication (2021)
The Supreme Court is not a trier of facts; it rejects petitions for review attended by factual questions. However, not all factual assertions are necessarily the subject of trial. Adjudicative factsthe material incidents of a case-are contingent on evidence. Parties' conflicting claims on what transpired must be weighed during trial. The same is not true of legislative facts-more generalized facts about the world that transcend a particular dispute. Rather than impair, descriptive knowledge on such matters as science, history, economics, culture, or psychology can facilitate the resolution of questions of law by weighing law's contents and considerations, ultimately enabling a determination of what the law is or how it ought to be interpreted. Instead of a sweeping rejection of cases that deal with questions of a factual sort, this Article invites recognition: first, of the distinction between adjudicative facts and legislative facts; and second, of the utility of considering legislative facts in the Supreme Court's discharge of its functions. This is especially true in the context of the Court's extraordinary capacities enabled by the 1987 Constitution's expansion of judicial power. This Article further considers challenges and pitfalls, along with responses and techniques to confronting legislative facts, particularly in an environment of information saturation and post-truth discourse.
Keywords: Supreme Court. Philippines; Administrative procedure